PENGARUH ATMOSFIR TOKO DAN PELAYANAN TERHADAP NILAI HEDONIK DAN PEMBELIAN TIDAK TERENCANA PELANGGAN INDOMARET SURAKARTA - Supriyono .; Dibyo Iskandar (AKTUAL, 2016)
This study aims are to determine the effect of atmospheric shops and service to purchase unplanned (impulsive buying) through hedonic value as an intervening variable. This research is a survey with a sample of 100 respondents Indomaret. Teknik analysis used the customer is using t-test, f, R test and path analysis. The analysis showed that in the first equation indicates that the store's atmosphere significantly influence the hedonic value and service shop also significantly influence the hedonic value. The second equation shows that the atmosphere of the store significant negative effect on impulsive purchases, service shops are also significant negative effect on purchases of indirect impulsive, second equation atmosphere of the store through the hedonic value amounted to 0.187 greater than the immediate value -0.220 and service shops to impulsive purchases through by hedonic values to 0.402. So hedonic value as intervening effectively. Keywords: atmospheric shops, service shops, hedonic value, unplanned purchases.